The characteristics and roles of antimicrobial peptides as potential treatment for antibiotic-resistant pathogens : a review - Zainal Baharin, Nurul Hana; Khairil Mokhtar, Nur Fadhilah; Mohd Desa, Mohd Nasir; Gopalsamy, Banulata; Mohd Zaki, Nor Nadiha; Yuswan, Mohd Hafis; Muthanna, AbdulRahman; Dzaraly, Nurul Diana; Abbasiliasi, Sahar; Mohd Hashim, Amalia; Abdullah Sani, Muhamad Shirwan; Mustafa, Shuhaimi (O'Reilly and SAGE, 2021)
The emergence of antibiotic-resistant bacteria has become a significant and everincreasing threat to global public health, increasing both morbidity and mortality rates, and the financial burden on health services. Infection by drug-resistant bacteria is anticipated to contribute to the demise of almost 10 million people by the year 2050 unless a competent and effective response is devised to engage with this issue. The emergence and spread of resistance are commonly caused by the excessive or inappropriate use of antibiotics and substandard pharmaceuticals. It arises when pathogens adapt to different conditions and develop self-defence mechanisms. Currently, novel antimicrobial peptides (AMPs) have been reported to be the sole cure for some clinical cases of infectious diseases such as sepsis and skin infections, although these agents may, on occasion, require administration together with an adjunctive low-dose antibiotic. Although AMPs are a promising alternative form of anti-microbial therapy and easily applied in the medical sector, they still have limitations that should not be taken lightly. Hence, this review explores the characteristics, advantages and disadvantages of AMPs for their potential in treating antibiotic-resistant pathogens.